Understanding Natural Symptoms Through a Scientific Approach in Kindergarten Boys III Bangko, Merangin Regency - Fithri Azni (Peneliti.net, 2022)
This research is related to natural phenomena and it is necessary to find an appropriate approach or learning method, one of which is to use a scientific approach. This study aims to